1983
DOI: 10.1104/pp.72.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Stomatal Conductance of Potato Clones (Solanum tuberosum L.)

Abstract: A few potato lone, such as A6948-4, had higher rates ofphotosynthesis in the f than the Russet Burbank and were able to maintain higher rates not only dring miday but also in the early mornng and late evning For many species, more than 95% of the plant dry weight is derived from photosynthetically fixed CO2 (17). Many physiologists have studied rates of photosynthesis in various crops, and some have found differences in photosynthetic rates. For example, Bhagsari and Harmon (2) reported differences in rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
3
9
0
1
Order By: Relevance
“…The morphological responses were similar to the continuous illumination injury described by Cao and Tibbitts (1991). The A net values of leaves grown under HL conditions were comparable to A net values previously reported for plants of comparable ages and grown under similar environmental conditions (Dwelle et al, 1983).…”
Section: Net Carbon Assimilationsupporting
confidence: 88%
“…The morphological responses were similar to the continuous illumination injury described by Cao and Tibbitts (1991). The A net values of leaves grown under HL conditions were comparable to A net values previously reported for plants of comparable ages and grown under similar environmental conditions (Dwelle et al, 1983).…”
Section: Net Carbon Assimilationsupporting
confidence: 88%
“…This is the basis for the search for high rates of photosynthesis as proposed by Dwelle et al (1983). However, in our studies correlations between rates of photosynthesis and RGR, NAR, and TDWT were generally low, with the exception of batches including non-tuberosum species (III, V, VI, VII - Table 3).…”
Section: Discussionmentioning
confidence: 38%
“…It must be noted that we evaluated the responses of photosynthesis and conductance to a level of irradiance that is approximately equivalent to two third of full sunlight. However, Dwelle et al [3] reported field observations showing that conductance of potato leaves still continued to increase with radiation when photosynthesis was already saturated. In line with their results we measured with a crop enclosure [1] a constant ratio of circa 0.01 g CO2 g-~ H20 between the rates of photosynthesis and transpiration when irradiance varied between circa 35 and 350Win -2 (PAR) (Vos, unpublished).…”
Section: Effects Of Irradiancementioning
confidence: 99%